Just be gorgeous : a novel - Wersba, Barbara (New York : Harper & Row, 1988)
Feeling unattractive, untalented, and misunderstood by her parents, a New York City teenager realizes that she is someone special through her friendship with a homeless street performer.
"A Charlotte Zolotow book."
Keywords: Self-esteem -- Fiction; Friendship -- Fiction; Parent and child -- Fiction; New York (N.Y.) -- Fiction